Ambiguity tolerance towards learning English as a foreign language and accuracy of oral speech - Ghadah Al Murshidi; Zalik Nuryana (Association for Scientific Computing Electrical and Engineering(ASCEE), 2024)
All languages contain inherent ambiguities, and foreign language learners often encounter various uncertainties when learning a new language. Ambiguity tolerance is a crucial personality trait that can significantly influence the foreign language learning process. Over time, ambiguity tolerance has gained importance due to its impact on different aspects of language learning. This study investigates the relationship between ambiguity tolerance, the optimal choice of language learning approaches, and the degree of anxiety in learning English as an additional foreign language. The research was conducted with graduate and undergraduate students from the United Arab Emirates University, specifically those studying in the education field and enrolled in an English foreign language learning course. A quantitative Google survey was administered, gathering data from 270 students, which was subsequently analyzed using SmartPLS 3. The results revealed that ambiguity tolerance is negatively associated with students' anxiety levels and positively correlated with their choice of language learning strategies, ultimately enhancing their oral speech accuracy. This study offers valuable insights for academicians to design strategies that promote ambiguity tolerance among learners, thereby boosting their motivation and reducing anxiety levels. It also contributes significantly to the body of knowledge for researchers in this field.